Branding and selling public transit in North America: An analysis of recent messages and methods. (March 2016) - Hess, Daniel Baldwin; Bitterman, Alex
Abstract: Branding, marketing, and advertising play important roles in influencing travel behavior and shaping public opinion about public transit. In recent years, marketing efforts in North America have increasingly featured messages that promote the value of riding public transit. These campaigns underscore a somewhat broader marketing effort that seeks to distinguish public transportation as a better value than commuting by automobile, a position that is bolstered by a weak international economy, fuel price fluctuations, and growing public awareness and concern about environmental issues. For many public transit managers, marketing falls outside the realm of necessary operations and becomes unimportant relative to other more principal tasks. The unmet need for critical examination of public transportation marketing efforts leaves the efficacy of public transit marketing efforts untested, which is evidenced by both a gap in academic literature that distills best practices but also a gap in professional practice that demonstrates a reluctance to spend scarce resources on marketing. Because of this complex landscape, the long-term value of public transit marketing relative to marketing efforts across other transportation sectors is unclear. This study examines the proliferation of value-oriented advertising messages, environmental brand designs, and vehicle livery, and specifically the planning and administration of branding efforts. A critical analysis of advertising messages across a select number of North American public transit markets yields a typology that uncovers contemporary advertising practices. We examine best practices and short-term outcomes of advertising in response to situations external to a public transit agency from which transit managers can objectively evaluate future efforts.